2021
DOI: 10.1016/j.isci.2020.101896
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response modules characterize IL-1β and IL-6 activity in COVID-19

Abstract: Dysregulated IL-1β and IL-6 responses have been implicated in the pathogenesis of severe Coronavirus Disease 2019 (COVID-19). Innovative approaches for evaluating the biological activity of these cytokines in vivo are urgently needed to complement clinical trials of therapeutic targeting of IL-1β and IL-6 in COVID-19. We show that the expression of IL-1β or IL-6 inducible transcriptional signatures (modules) reflects the bioactivity of these cytokines in immunopathology modelled by juven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…Recently, early results released from the Randomised, Embedded, Multifactorial, Adaptive Platform Trial for Community-Acquired Pneumonia (REMAP-CAP) international platform trial showed that tocilizumab was effective in critically ill patients. 3 In an observational study 4 in the Reggio Emilia area, considering 172 patients consecutively treated with tocilizumab, the percentage of patients who died after tocilizumab therapy was similar to that of patients with COVID-19 hospitalized in the same time period and not treated with tocilizumab after a follow-up of more than 1 month. However, when some of our researchers considered the subgroup of patients undergoing noninvasive ventilation, tocilizumab reduced the risk of being intubated or dying.…”
Section: Tocilizumab In Treatment For Patients With Covid-19mentioning
confidence: 85%
See 3 more Smart Citations
“…Recently, early results released from the Randomised, Embedded, Multifactorial, Adaptive Platform Trial for Community-Acquired Pneumonia (REMAP-CAP) international platform trial showed that tocilizumab was effective in critically ill patients. 3 In an observational study 4 in the Reggio Emilia area, considering 172 patients consecutively treated with tocilizumab, the percentage of patients who died after tocilizumab therapy was similar to that of patients with COVID-19 hospitalized in the same time period and not treated with tocilizumab after a follow-up of more than 1 month. However, when some of our researchers considered the subgroup of patients undergoing noninvasive ventilation, tocilizumab reduced the risk of being intubated or dying.…”
Section: Tocilizumab In Treatment For Patients With Covid-19mentioning
confidence: 85%
“…Third, IL-6 is a pleiotropic cytokine with both pro-inflammatory and anti-inflammatory properties and is also involved in antiviral responses. 4 According to pharmacokinetic studies, lower-dose tocilizumab blocks IL-6 binding to its soluble receptor, and thus inhibits pro-inflammatory response, while high-dose tocilizumab may bind to both soluble and membrane-bound IL-6 receptors and inhibit both pro-inflammatory and anti-inflammatory pathways. 5 Taken together, low-dose tocilizumab may be a better option to reduce IL-6-related cytokine storm and mortality in patients with COVID-19.…”
Section: Tocilizumab In Treatment For Patients With Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, we could not investigate PCT as it was not measured routinely in our CAP cohorts. Future studies should assess the discriminatory capacity of PCT, D-dimers, 9 , 24 , 34 and other novel biomarkers, such as transcriptional signatures that quantify inflammatory cytokine activity 35 or those that discriminate bacterial from viral infections. 36 …”
Section: Discussionmentioning
confidence: 99%